PERANAN IBU DALAM KELUARGA PADA NASKAH DRAMA AYAHKU PULANG KARYA USMAR ISMAIL - Wewet Monica Fitri; Syeilendra (Universitas Negeri Padang, 2025)
This study aims to describe and analyze the role of mothers in maintaining emotional, social, and moral balance in the family as depicted in the drama script Ayahku Pulang by Usmar Ismail. The mother character in this drama shows determination, patience, and wisdom in facing family conflicts due to the departure and return of her husband who has long left home. This type of qualitative research with a descriptive analysis approach, the theories used are the social role theory of Soerjono Soekanto and the family psychology theory of Singgih D. Gunarsa. The data collection technique is by literature study and documentation, while the data analysis technique is by the researcher reading the drama script Ayahku Pulang by Usmar Ismail repeatedly, carefully, and critically, the researcher marks parts of the text, such as dialogue or narrative that contains the role of mothers in the family, grouping data based on relevant themes, according to each role, the data is entered into a data collection format in the form of a table that helps researchers in compiling data systematically, then compiling the results of the analysis into a narrative that answers the formulation of the research problem. The research data was obtained from excerpts of dialogue and narrative in the drama script, which were analyzed based on indicators of the mother's role in maintaining family balance: emotional, social, and moral. The results show that the mother plays a crucial role as a caregiver who calms children in emotional situations, as a mediator in maintaining social relations between father and child, and as a guardian of moral values ​​within the family. This role reflects the mother's role as the center of family resilience, remaining strong amidst conflict and the absence of a father figure. These findings emphasize that literary works, particularly drama, can reflect family values ​​relevant to the realities of society. The mother character in this script represents a strong, wise woman who plays a significant role in maintaining family unity.